What you have above would work, but your notation is awful! Try to use the notation as given in the problem. Also notice that uppercase letters represent matrices, and lowercase letters represent the entries in a matrix.
View attachment 50857
The Attempt at a Solution
-(y, x) = -(YX-XY)
Can I do this or would I have to define a matrix X= ( a b c d ) Y= ( e f g h)
And prove it that way? I am just really confused
This is easier to follow.[X, Y]= YX- XY
Thus [Y, X]= XY- YX
then -[Y, X]= -(XY- YX)
then -[Y, X]= -XY +YX
Like that? So i don't have to use matricies with variables, just use X and Y to represent a matrix?